ANALISIS STABILITAS DINDING PENAHAN TANAH TIPE KANTILEVER PADA ABUTMENT JEMBATAN TERHADAP MUKA AIR BANJIR - Jovanda Anggie Hirza Rivansyah; Dian Purnamawati Solin; Bagas Aryaseta (Racic : Rab Construction Research, 2026)
Retaining walls play a crucial role in road and bridge infrastructure by resisting lateral earth pressure and preventing slope failure or damage caused by rising river water levels. This study compares the stability of gabion-type and cantilever-type retaining walls through manual calculations and numerical simulation using Geo5 software. The analysis focused on overturning, sliding, bearing capacity, and slope stability under both normal and flood water level (MAB) conditions. Manual calculations indicated that both wall types satisfied stability requirements with safety factors of 0.96–2.07 for overturning, 2.01–3.53 for sliding, and 6.89–6.92 for bearing capacity. However, Geo5 analysis showed that gabion walls were only safe in terms of overturning (6.70–7.50) and sliding (2.12–2.30), while bearing capacity (0.57–0.80 < 3.0–3.5) and slope stability (1.33–1.37 < 1.5) did not meet the required standards. In contrast, cantilever walls proved safe across all parameters, with safety factors of 7.25–9.87 for overturning, 2.09–2.48 for sliding, 3.14–4.90 for bearing capacity, and 1.52–1.69 for slope stability. Therefore, reinforced concrete cantilever retaining walls are more suitable as an effective and reliable alternative to gabion walls, particularly in flood-prone and landslide-prone areas.